Tokamak Engineering Mechanics - Song, Yuntao. (Mechanical Engineering Series,, 2014)
Tokamak Engineering Mechanics offers concise and thorough coverage of engineering mechanics theory and application for tokamaks, and the material is reinforced by numerous examples. Chapter topics include general principles, static mechanics, dynamic mechanics, thermal fluid mechanics and multiphysics structural mechanics of tokamak structure analysis. The theoretical principle of the design and the methods of the analysis for various components and load conditions are presented, while the latest engineering technologies are also introduced. The book will provide readers involved in the study of mechanical/fusion engineering with a general understanding of tokamak engineering mechanics.   Yuntao Song is Head of the Tokamak Design Division at the Institute of Plasma Physics, Chinese Academic of Science (ASIPP), China.